Addressing work-from-home challenges through rural coworking - Tjernberg, Michaela (Frontiers in Organizational Psychology, 2025)
Public employees request a hybrid workplace solution. However, to some employees, working from home poses challenges such as a lack of an office infrastructure and feelings of loneliness. To overcome these challenges and secure decent work conditions during remote work, the private sector, and freelancers have used local coworking spaces (CWSs). With the increase of hybrid work arrangements, the public sector needs to ensure that employees have decent onsite and remote working conditions, in which CWSs could function as an alternative to home-based work. Through a 1-year qualitative evaluation project, 15 public employees tested hybrid work in which they combined work at the centralized office, from home, and at a local CWS. Data were collected through surveys with open-ended questions and semi-structured interviews. The results from the content analysis show a diverse picture of participants' perceptions regarding the use of CWSs. When there was a lack of users and a decent physical work environment, public employees preferred to work from home. On the contrary, when adequately designed, CWSs provided employees with social interactions and became an integral part of the local community. These findings suggest that introducing local CWSs can promote sustainable work if they align with employees' needs.